Kinetics and Thermodynamics of Constitutional Dynamic Coordination Systems Based on FeII, CoII, NiII, CuII, and ZnII. Issue 24 (22nd July 2016) - Neranon, Kitjanit; Ramström, Olof
Abstract : The self‐adaptation of constitutional dynamic systems based on selective coordination between 5, 5′‐dimethyl‐2, 2′‐bipyridine and deuterium‐labeled 4, 4′‐dimethyl‐2, 2′‐bipyridine to Fe II, Co II, Ni II, Cu II, or Zn II has been evaluated by ESI‐MS in methanol. The equilibration rates of the systems proved dependent on the metal species, following the order Zn II > Cu II > Co II > Ni II > Fe II, where Zn II resulted in rapid rearrangement of the original homoleptic complexes. The heteroleptic complexes were favored in the systems with Co II, Cu II and Zn II, whereas the homoleptic complexes were more pronounced with Fe II and Ni II . Abstract : The constitutional dynamics of adaptive coordination systems based on Fe II, Co II, Ni II, Cu II, and Zn II has been evaluated by ESI‐MS and NMR. The resulting dynamic equilibration processes could be easily followed over time, and the kinetic and thermodynamic properties assessed.